2023
DOI: 10.3390/healthcare11050717
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development of a Patient Reported Experience Measure for Older Adults Attending the Emergency Department: Part I—Interviews with Service Users

Abstract: Older adults are a major Emergency Department (ED) user group who may be especially vulnerable to the consequences of crowding and sub-optimal care. Patient experience is a critical component of high-quality ED care and has previously been conceptualised using a framework focusing on patients’ needs. This study aimed to explore the experiences of older adults attending the ED in relation to the existing needs-based framework. Semi-structured interviews were conducted during an emergency care episode with 24 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…An initial list of candidate items was developed by two researchers (B. G. and J. M. L.) following methodological triangulation of findings from prior studies conducted by the research team. These consisted of a qualitative metasynthesis of 22 studies of patient experience in the ED 17 ; interviews conducted with 24 patients aged over 65 attending the ED 18 ; and interprofessional focus groups with 37 ED staff 19 . Methodological triangulation describes the use of multiple data sources to study a phenomenon, and is useful to confirm findings, enrich data and increase overall validity 20 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial list of candidate items was developed by two researchers (B. G. and J. M. L.) following methodological triangulation of findings from prior studies conducted by the research team. These consisted of a qualitative metasynthesis of 22 studies of patient experience in the ED 17 ; interviews conducted with 24 patients aged over 65 attending the ED 18 ; and interprofessional focus groups with 37 ED staff 19 . Methodological triangulation describes the use of multiple data sources to study a phenomenon, and is useful to confirm findings, enrich data and increase overall validity 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Confirmation of conceptual validity and expansion of the framework was then achieved by undertaking semi-structured interviews with older adults during an emergency care episode, and focus groups with staff responsible for the provision of emergency care to older adults across three EDs. 18,19 This study aims to describe the process of generating and prioritising a list of suggested items for PREM-ED 65 by involving multiple stakeholders including patient and public representatives, healthcare professionals and advocates for older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation